Strengthening Awareness of Post-Identity as Asset for Society 5.0 through Reflective Learning - Danan Tricahyono (Badan Pembinaan Ideologi Pancasila, 2022)
The background of this article departs from the development of the times that provide opportunities and challenges to humanity in facing the era of society 5.0. The purpose of writing this article is to strengthen post-identity awareness through reflective learning in the subject of civic education (Pkn). The writing of this article uses conceptual ideas. Society 5.0 wants to create a community that truly enjoys life. Social reform in society 5.0 will create an ever-changing society by having foresight, a society that upholds tolerance, and a society where every person can lead an active and enjoyable life. Reflective learning has five hierarchies of thought processes, including 1) reporting, 2) responding, 3) relating, 4) reasoning and 5) reconstructing. Reflective learning strengthens the post-identity awareness of students in the face of the era of society 5.0. Post-identity consciousness has a relationship with the concept of global diversity. To achieve global diversity, students must be able to reflect and be responsible for the experience of diversity and social justice. This post-identity awareness is capital for strengthening tolerance and caring for Indonesian pluralism to welcome the life of the society 5.0 era. The direction of civic education and society 5.0 has the same mission of realizing a humanist order of society.